Effect of thermal aging on mechanical performance of GF/PBT composites for high voltage bushing - Qianli Wang; Liying Zhou; Xin Shang; Tianxiang Duanmu; Huimin Ma (Discover Applied Sciences)
Abstract The present work aims to study the mechanical performance of glass fiber reinforced polybutylene terephthalate (GF/PBT) composite materials used for high-pressure casing under different thermal aging temperatures. With the increasing demand for durable materials in high-temperature environments, it is crucial to understand how thermal aging affects the structural integrity of these composites. Both tensile and three-point bending tests are conducted on the thermally aged GF/PBT samples. Meanwhile, the stress analysis is performed using the finite element method, and the tensile fracture morphology and mode are observed using a scanning electron microscope. The findings delineate a marked reduction in tensile strength by up to 22% and bending strength by up to more than 5% as the aging temperature increased. The specimens exhibit diminished plasticity, while the elastic modulus remains largely invariant (2.4 GPa) across the tested temperature range, demonstrating resilience to thermal aging. High-resolution SEM microscopy of the tensile fracture surfaces confirms that the fracture behavior of the thermally aged composite leans towards brittleness. Moreover, thermal aging accentuates the detachment of glass fibers from the PBT matrix during tension, manifesting as pits on the matrix surface and interfacial discrepancies and fissures between the glass fibers and the matrix.